“Cuidado de enfermería en adultos en situación de crisis en el contexto hospitalario, con enfoque en la contención verbal: Una revisión narrativa de la literatura.” (2022)
The intervention of the nursing professional in a context where a person presents a crisis situation, where the risk of psychomotor agitation increases is essential, therefore, it must be clear and concise, knowing this, a narrative review of the literature is necessary, to make a description of the publications related to the nursing intervention in the verbal restraint, to guarantee the humanized attention of the care subject. The foregoing, following the parameters established by the mental health laws of Colombian public policy. This work also aims to promote attitudes that result in a correct modulation of the affected person, where the use of physical and / or pharmacological methods is not necessary to achieve this objective.